Geographies of privilege - Twine, France Winddance; Gardener, Bradley (Routledge, 2013)
How are social inequalities experienced, reproduced and challenged in local, global and transnational spaces? What role does the control of space play in distribution of crucial resources and forms of capital (housing, education, pleasure, leisure, social relationships)? The case studies in Geographies of Privilege demonstrate how power operates and is activated within local, national, and global networks. Twine and Gardener have put together a collection that analyzes how the centrality of spaces (domestic, institutional, leisure, educational) are central to the production, maintenance and transformation of inequalities. The collected readings show how power–in the form of economic, social, symbolic, and cultural capital–is employed and experienced. The volume's contributors take the reader to diverse sites, including brothels, blues clubs, dance clubs, elite schools, detention centers, advocacy organizations, and public sidewalks in Canada, Italy, Spain, United Arab Emirates, Mozambique, South Africa, and the United States. Geographies of Privilege is the perfect teaching tool for courses on social problems, race, class and gender in Geography, Sociology and Anthropology.
Keywords: afrique; afrique du sud; amériques; anthropologie; approches et analyses; canada; classe sociale; discipline; environnement; espagne; europe; géographie; italie; mozambique; outils; ouvrages de références; privilèges; racisme; régions géographiques; sciences humaines; sexisme; sociologie; systèmes d'oppressions; thématiques; émirats arabes unis; états-unis

Les Autochtones au Canada: espaces et peuples en mutation - Desbiens, Caroline; Hirt, Irène (L'Information géographique, 2012)
Alors que les questions relatives à l’autochtonie ont longtemps été le domaine de l’anthropologie, nous assistons ces dernières années à un décloisonnement des recherches. La géographie participe activement à cette mouvance, notamment par la richesse de sa boîte à outils en ce qui concerne les questions de paysage, ressources, environnement et gouvernance territoriale. En commençant par un survol des aires culturelles autochtones en Amérique, nous proposons dans cet article d’identifier trois thèmes dominants en ce qui a trait aux espaces de l’autochtonie contemporaine au Canada : la gouvernance, les savoirs, et l’urbanité.
Keywords: amériques; approches et analyses; cours; discipline; géographie; har4600; histoire et politique; pol4105; premier cycle; premières nations; régions géographiques; sciences humaines; système colonial; systèmes d'oppressions; thématiques

Geography and gender: what belongs to feminist geography? Emotion, power and change - Sharp, Joanne (Progress in Human Geography, 2009)
Keywords: approches et analyses; discipline; discours dominant; genre; géographie; ressource en ligne; sciences humaines; systèmes d'oppressions; émotions